Speech emotion detection using supervised, unsupervised and feature selection algorithms - Rifat, Abu Nuraiya Mahfuza Yesmin; Biswas, Aditi; Chowdhury, Nadia Farhin (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.